Approximate asymptotic variance-covariance matrix for the whittle estimators of GAR(1) parameters - Shitan, Mahendran; Peiris, Shelton (Taylor & Francis, 2013)
Generalized Autoregressive (GAR) processes have been considered to model some features in time series. The Whittle's estimates have been investigated for the GAR(1) process by a simulation study by Shitan and Peiris (2008). This article derives approximate theoretical expressions for the enteries of the asymptotic variance-covariance matrix for those estimates of GAR(1) parameters. These results are supported by a simulation study.